Transformational Leadership and Innovative Work Behavior to Realize a Sustainable Organization: Case Study at the Wajo Regency Education Office - Herlina, Besse; Syamsiar, ‎ (KnE Social Sciences, 2025)
This research examines the influence of transformational leadership on innovative work behavior (IWB) and its implications for organizational sustainability, with a case study at the Wajo District Education Office. In the face of dynamic change and increasing demands in the public sector, adaptability and innovation have become critical. Drawing on Bass and Riggio’s (2006) four-dimensional framework—idealized Influence, inspirational motivation, intellectual stimulation, and individualized consideration—the study analyzes how leadership shapes employees’ creativity, engagement, and willingness to generate and implement new ideas. Using a quantitative explanatory design, data were collected from 49 civil servants through a structured questionnaire and analyzed using multiple linear regression and Bayesian ANOVA. Results indicate that charismatic leadership (β = 0.415; P < 0.01) and individualized consideration (β = 0.284; P < 0.05) significantly enhance organizational performance sustainability. Meanwhile, although several mediation paths were statistically nonsignificant, IWB emerged as a key mediating variable, reinforcing the link between leadership and sustainable outcomes. These findings confirm that transformational leadership plays the dual role of directly encouraging innovation through behavioral influence and indirectly sustaining performance by fostering an environment of psychological safety, creativity, and learning. The strong posterior support for models including individualized consideration (P(M|data) = 0.940) underscores the strategic value of personalized leadership approaches in bureaucratic contexts. The study highlights the importance of leadership development initiatives focused on strengthening transformational capabilities, particularly in motivating innovation and empowering employees. This approach can enhance organizational agility, resilience, and long-term relevance in the public sector.